Strategic modeling of enterprise business processes for successful digital transformation - Rustenova, Elvira; Ibyzhanova, Aizhan; Akhmetzhanova, Nazym; Talapbayeva, Gulnar; Yerniyazova, Zhanat; Aidaraliyeva, Aizhamal (Business, Management and Economics Engineering, 2025)
Purpose – the purpose of this study is to develop a methodology for modelling business processes based on the principles of process management and the use of modern information technology in order to improve the efficiency and quality of the enterprise.Research methodology – in this work we applied the methodology of business process analysis and optimisation based on the decomposition principle proposed by the SADT methodology. Findings – the result of the study was the development of practical recommendations for enterprises seeking to improve the efficiency of their activities and adapt to rapidly changing market conditions. The proposed methodology of business process modeling allows organi- zations not only to standardize and optimize their processes, but also to respond flexibly to changes in the external environment and maintain competitiveness.Research limitations – The study focuses primarily on SADT and IDEF0 methodologies, which may limit consideration of other potentially effective approaches to business process mode- ling. Future research may include a comparative analysis of different business process modeling methodologies to determine their relative effectiveness and applicability in different contexts.Practical implications – overall, this study makes a significant contribution to the development of modern business process modeling methodology, providing practical tools and recommendations for organizations seeking to improve their performance and sustainability in a rapidly changing business environment.Originality/Value – the novelty of this study lies in the development of an integrated methodology of business process modeling based on the principles of process management and modern information technologies. In contrast to earlier studies emphasizing individual aspects of process management or specific technologies, our study offers an integrated approach combining both managerial and technological elements.